2019
DOI: 10.5194/hess-23-4561-2019
|View full text |Cite
|
Sign up to set email alerts
|

Spatially distributed sensitivity of simulated global groundwater heads and flows to hydraulic conductivity, groundwater recharge, and surface water body parameterization

Abstract: In global hydrological models, groundwater storages and flows are generally simulated by linear reservoir models. Recently, the first global gradient-based groundwater models were developed in order to improve the representation of groundwater-surface-water interactions, capillary rise, lateral flows, and human water use impacts. However, the reliability of model outputs is limited by a lack of data and by uncertain model assumptions that are necessary due to the coarse spatial resolution. The impact of data q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Recently, improvements have been made towards to coupling groundwater models below LSMs and global hydrological models (e.g., de Graaf et al, 2017; de Graaf, Sutanudjaja, Van Beek, & Bierkens, 2015; Fan, Li, & Miguez‐Macho, 2013; Fan & Miguez‐Macho, 2011; Ganji & Sushama, 2018; Gedney & Cox, 2003; Gulden et al, 2007; Gutowski Jr et al, 2002; Guzman et al, 2015; Koirala, Kim, Hirabayashi, Kanae, & Oki, 2019; Maxwell et al, 2011; Maxwell & Miller, 2005; Niu, Yang, Dickinson, Gulden, & Su, 2007; Reinecke et al, 2019; Tian et al, 2020; Tian, Li, Wang, & Hu, 2012; Vergnes & Decharme, 2012; Yeh & Eltahir, 2005a, 2005b; York, Person, Gutowski, & Winter, 2002; Zeng et al, 2018). These studies generally showed that adding the groundwater component led to a more realistic partitioning of water components at the land surface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, improvements have been made towards to coupling groundwater models below LSMs and global hydrological models (e.g., de Graaf et al, 2017; de Graaf, Sutanudjaja, Van Beek, & Bierkens, 2015; Fan, Li, & Miguez‐Macho, 2013; Fan & Miguez‐Macho, 2011; Ganji & Sushama, 2018; Gedney & Cox, 2003; Gulden et al, 2007; Gutowski Jr et al, 2002; Guzman et al, 2015; Koirala, Kim, Hirabayashi, Kanae, & Oki, 2019; Maxwell et al, 2011; Maxwell & Miller, 2005; Niu, Yang, Dickinson, Gulden, & Su, 2007; Reinecke et al, 2019; Tian et al, 2020; Tian, Li, Wang, & Hu, 2012; Vergnes & Decharme, 2012; Yeh & Eltahir, 2005a, 2005b; York, Person, Gutowski, & Winter, 2002; Zeng et al, 2018). These studies generally showed that adding the groundwater component led to a more realistic partitioning of water components at the land surface.…”
Section: Introductionmentioning
confidence: 99%
“…The GLHYMPS2.0 provides permeabilities that are higher than the original values but still show the same inconsistencies as it uses the same surface lithology map (GLiM Hartmann & Moosdorf, ). These inconsistencies have a major impact on model results of water table depths, water table fluctuations, and head declines when storage is changed (de Graaf et al, ; Maxwell et al, ; Reinecke et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We further note that large-scale models have only been assessed to a very limited degree with respect to understanding, quantifying, and attributing relevant uncertainties. Expanding computing power, developing computationally frugal methods for sensitivity and uncertainty analysis, and potentially employing surrogate models can enable more robust sensitivity and uncertainty analysis such as used in regional-scale models (Habets et al, 2013;Hill, 2006;Hill & Tiedeman, 2007;Reinecke et al, 2019b). For now, we suggest applying computationally frugal methods such as the elementary effect test or local sensitivity analysis (Hill, 2006;Morris, 1991;Saltelli et al, 2000).…”
Section: How To Improve the Evaluation Of Large-scale Groundwater Modelsmentioning
confidence: 99%
“…In mountain regions, large-scale models tend to underestimate steady-state hydraulic head, possibly due to over-estimated hydraulic conductivity in these regions, which highlights that model performance varies in different hydrologic landscapes. (de Graaf et al, 2015;Reinecke et al 2019b). Additionally, there are significant regional differences in performance with low flows for a number of large-scale models (Zaherpour et al 2018) likely because of diverse implementations of groundwater and baseflow schemes.…”
Section: How To Improve the Evaluation Of Large-scale Groundwater Modelsmentioning
confidence: 99%